Responsabilidad social empresarial de la industria de tabacalera en Colombia: ¿Es una estrategia? (2015)
This research focuses on Corporate Social Responsibility (CSR) by tobacco companies in order to answer whether these companies used CSR initiatives in Colombia as a strategy to enhance the corporate image and counter their bad reputation, as part of its strategy to prevent further advances in regulation. I used a qualitative data analysis to process the documents available on its official internet pages and major national media between 2008 and 2011. The most important conclusion is that the tobacco companies appear as a strategic partner in efforts for development of the country, with two possible objectives: to improve their image and gain influence in political processes. It is necessary to consider these strategies especially in light of the scope of the ban to sponsorship and promotion that the industry has.